Fish oil alters tamoxifen-modulated expression of mRNAs that encode genes related to differentiation, proliferation, metastasis, and immune response in rat mammary tumors - Bidinotto, Lucas Tadeu (2012)
We have previously shown that a fish oil-rich diet increased the chemopreventive efficacy of tamoxifen (Tam) against N-methyl-N-nitrosourea (MNU)-induced rat mammary carcinogenesis. Herein, we provide evidence that tamoxifen treatment modifies gene expression of mammary tumors depending upon the type of dietary fat fed to the animals. Rats initiated with MNU and treated with Tam were fed a diet rich in corn oil (CO) or fish oil (FO). After 8 weeks, cribriform tumors were collected and gene expression analysis was performed. Increased RNA expression of genes such as SerpinB10, Wisp2 and Apod in tumors from FO-treated rats is indicative of highly differentiated tumors. Decreased expression of H19 and Igf2 mRNA in Tam-treated groups, and Sncg mRNA in FO+Tam group may be related to tumor growth impairment and lower metastatic capacity. Change in the expression of genes associated with immunity in animals in the FO+Tam group may suggest a shift in the immune response. These data show that, although tamoxifen modulates the expression of genes leading to tumor growth impairment, further modulations of genes are influenced by FO. FO modulation of Tam changes in gene expression accounts for its enhancing chemopreventive effect against MNU-induced mammary carcinogenesis.